Superconducting Devices for Radioastronomy; First Steps in Chile: SNS-junction Fabrication - Conte, V.; Giordano, J.L.; Zarate, J.J.; Luzuriaga, J. (The National Radio Astronomy Observatory, 2010)
Fil: Zarate, J.J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina